Nursing and collaborative diagnoses on perioperative patients with and without using six steps of diagnostic reasoning methods - Suarni, Lisa; Nurjannah, Intansari; Apriyani, Heni (International Journal of Research in Medical Sciences, 2017)
Background: Perioperative is a term that involving three different phases of surgery which are pre-operative phase, intraoperative phase and post-operative phase. Each phase is started and ended in the specific time with the sequence of events that shape patient experience related to surgery.This research is aimed at identifying the different types of nursing diagnosis and collaborative diagnosis on perioperative patients with and without using 6 steps of diagnostic reasoning method. Methods: This is a descriptive quantitative research. Respondents of the research were 52 perioperative patients and 12 nurses. Results: The less number of diagnoses were established without using 6 steps of diagnostic reasoning method. It is found that more various diagnoses established by using 6 steps of diagnostic reasoning method and more heterogenic diagnoses found in preoperative status than in intra and post-operative status. Specific diagnoses also only appear in a specific type of anesthesia. Conclusions: There are differences between the variation and number of nursing diagnoses enforced by nurses on perioperative patients with and without using the 6 steps in diagnostic reasoning method.